THE LEVEL OF THE PRIMARY SCHOOL ADMINISTRATORS’ ETHIC LEADERSHIP BEHAVIOR - Mehmet Akif HELVACI (Zeitschrift für die Welt der Türken, 2010)
The aim of this research is to state primary shool administrators` ethic behaviours according to teachers` opinions. Ethic Leadership Scale developed by Yılmaz (2005) was used to collect the data for the research. The population of the research is teachers working in primary schools in Uşak province and it`s districts (Banaz, Ulubey, Sivaslı). According to the opinions of the teachers who participated in this research, it can be seen that primary school administrators` ethic leadership shows behaviours at a middle level in the communicative ethic, decisional ethic in organizations, behavioral ethic and climatical ethic dimensions.